Neural Network for Modeling of Chemical Reaction Systems: Kinetics of Concentrated Acid Hydrolysis of Walnut Green Skin - Arasteh Nodeh, A.; Ardjmand, M.; Fanaei, M.A.; Safekordi, A.A. (Asian Journal of Chemistry, 2012)
Besides usage of walnut green skin as an available biomass for bioethanol production, application of neural network for modeling the conversion rates of glucose from walnut green skin by concentrated acid hydrolysis has been investigated. Due to a more complex and unknown kinetics of the investigated reaction, the proposed approach based on application of neural networks is an efficient and accurate tool to solve modeling problem. The influence of the main pretreatment variables including temperature, processing time, solid contents and acid concentration on fermentable sugar generation from walnut green skin is studied by using factorial design of experiment. Levels for pretreatment temperature (65, 80, 90 ºC), process time (120, 180, 240 min), solid content (5, 10, 15 %) and concentration of sulfuric acid (20, 40, 60 %) were selected. Glucose were analyzed by HPLC and modeled by two layers neural network with different topology. Despite using simple data and a simple neural network, high accuracy was achieved. Results was compared with a quadratic equation model.